IMPROVING STUDENT'S INDEPENDENCE THROUGH MACROMEDIA FLASH-BASED LEARNING VIDEO STIMULUS - saipul Nuriman (Universitas Pendidikan Indonesia, 2022)
This research is motivated by the low level of learning independence of class XI students at SMA Negeri 10 Bandung in learning dance. One of the causes of the lack of a sense of independence in student learning is the lack of stimulus and learning media used by teachers are too monotonous, less innovative so that students become bored during the learning process in class. So that this study aims to apply macromedia flash-based dance learning videos in dance learning as a solution to the problems that occur so that students are able to utilize audio-visual technology as a learning medium to increase the learning independence of class XI students at SMA Negeri 10 Bandung. The method in this study uses quantitative research design, experimental research (quasi-experimental) with the type of method one group pre-test post-test. The instruments used are observation guidelines, questionnaires, interviews. The results of this study using pre-test and post-test can be proven that by applying macromedia flash-based dance learning videos can increase students' independent learning attitudes. The results before the action was carried out were in a less independent position and the results after the implementation of the action were in an independent position. The application of this macromedia flash-based learning video can not only improve independent attitudes in learning but can also improve learning outcomes, so it can be concluded that the application of this macromedia flash-based learning video can increase student learning independence.